PELATIHAN BAHASA JEPANG DASAR BAGI ANAK-ANAK TUKANG SUWUN DI PASAR BADUNG - OEINADA, I G; WIRIANI, N M; GIRI, NLK YULIANI; DEWI, NM ANDRY ANITA; DAMAYANTI, SILVIA; PURNAWATI, K WIDYA (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015)
This community service was intended to introduce Japanese language and culture to children who have profession as labor at Pasar Badung in Bali. Although they are in school-age, because of economic and other reasons, they have to give priority to economics activities rather than their own education. This community service was held by the staff and students of Japanese Department, Udayana University’s on Friday, August 01st, 08th, and 15th, 2014. The location is at Sanggar Belajar Anak Pasar Badung, 4th floor Pasar badung. The methods used in training Japanese language and culture to them were orientation, drills, and feedback. There were a lot of benefits obtained by the children from this community service activit, they can learn about basic Japanese language as well as Japanese culture via animated cartoons played during lunch breaktime. To the students as the assistant-instructors of this activity, can learn about real situation language teaching process and handle questions and overcome difficulties in the process. To the lecturers as the advisers of this activity, they can devote their knowledge as an implementation of Tri Dharma Perguruan Tinggi.